10-Vertex closo-carborane: a unique ligand platform for porous coordination polymers. Issue 12 (1st March 2016) - Boldog, Ishtvan; Bereciartua, Pablo J.; Bulánek, Roman; Kučeráková, Monika; Tomandlová, Markéta; Dušek, Michal; Macháček, Jan; De Vos, Dirk; Baše, Tomáš
Abstract : 1, 10-Dicarboxy-1, 10-dicarba- closo -decaborane, a classical dicarboxylate spacer ligand type similar to the prototypical terephthalic acid, proved to be different not only from the latter, but also from its closest 12-vertex relative, with regard to topology of its derived PCPs. Abstract : 1, 10-Dicarboxy-1, 10-dicarba- closo -decaborane, a classical dicarboxylate spacer ligand type similar to the prototypical terephthalic acid, proved to be different not only from the latter, but also from its closest relative compound, 1, 12-dicarboxy- closo -1, 12-dicarbadecaborane, with regard to the topology of its derived PCPs. Highly porous and robust compounds of zinc (rob net) and cobalt ('quasi'pcu ) as well as a topologically unexpected copper compound (lvt ) define the individuality of the 10-vertex carborane cage as a new fundamental spacer type in PCP chemistry. A combination of a lower steric demand compared to the 12-vertex analogue, a preferred orientation angle of 45° between the carboxylate planes and a moderately low rotation barrier are held responsible for the uniqueness of the 10-vertex analogue.